Dental Caries Experience and Salivary Elements Among A Group of Young Adults In Relation to Age and Gender - Abdel Aziz, Samara Faris; Al-Obaidi, Wesal Ali (Journal of Baghdad College of Dentistry, 2017)
ABSTRACTBackground: Dental caries is a most common social and intractable infectious disease in human. Saliva is critical for preserving and maintaining oral health and salivary elements had many effects on caries experience.Aim of study: This study was conducted to assess dental caries severity by age and gender and their relation to salivary zinc and copper among a group of adults aged (19-22) years.Materials and methods: After examination eighty persons aged 19-22 years of both gender. Caries severity was documented according to DMFS index. Stimulated salivary samples were collected and chemically analyzed under standardized condition to detect salivary elements zinc and copper. Concentrations of Zinc and copper were measured by using atomic absorption spectrophotometry.Results: The finding revealed that the total males had higher mean value of DMFS and DS fraction than that of the total females with statistically non-significant differences at p> 0.05 regarding of DMFS, while significant difference was found regarding DS fraction. Frist age group (19-20) had a lower mean value of DMFS than that of the second age group (21-22), while it had a higher mean value of DS fraction with statistically non-significant differences. There were statistically non-significant differences at p> 0.05 between males and females regarding salivary zinc and copper concentrations.Non-significant positive weak correlation between DMFS index and salivary zinc and copper.Conclusion: Saliva is the one of important factors in prevention of dental caries. Therefore, chemical changes in salivary composition play an important role in development and progression of caries.